2015
DOI: 10.5937/arhfarm1501072u
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of health literacy instruments which could be used on a primary healthcare level

Abstract: Kratak sadržajProcena zdravstvene pismenosti podrazumeva primenu različitih instrumenata kojima se određuje stepen razumevanja pročitanih ili verbalnih informacija, kao i numeričke sposobnosti neophodne za donošenje odgovarajućih zdravstvenih odluka. Cilj rada je da se identifikuju instrumenti koji se koriste za procenu zdravstvene pismenosti na nivou primarne zdravstvene zaštite, i da se komparativnom analizom njihove strukture utvrde mogućnosti primene za procenu zdravstvene pismenosti kod pacijenata u javni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…The most of instruments were applied in primary care setting (emergency department, waiting room at primary care) 3,14,[15][16][17][18] . Researchers agree that health literacy is related to the context, and different settings require different assessment tools 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The most of instruments were applied in primary care setting (emergency department, waiting room at primary care) 3,14,[15][16][17][18] . Researchers agree that health literacy is related to the context, and different settings require different assessment tools 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 33 These findings are confirmed by further studies, which have found that patients’ disease knowledge correlates with their perceived self-efficacy. 15 , 34 A low level of health literacy has a negative effect on the health of the patients concerned; 16 , 35 moreover, patients’ disease knowledge has an influence on their therapy adherence rate. 31 , 36 , 37 Based on a comprehensive meta-analysis and a review, the relationship between health literacy, adherence, and self-efficacy is inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…A szakirodalom szerint az egészségértés alacsony szintje negatívan befolyásolja az egészségi állapotot [27,28], kutatásunkban azonban ezt az összefüggést csak a BHLS esetén kaptuk meg. Ennek okát az alkalmazott tesztek típusában is kereshetjük: az önbevalláson alapulók egyfajta attitűdöt, hatékonyságérzetet is mérhetnek, míg a DKT2 objektív eredményt ad.…”
Section: Megbeszélésunclassified